Spontaneous rupture of a splenic artery aneurysm causing acute abdomen in a 19-year-old male patient: a case report - Njoum, Yumna; Barqawi, Abdallah Deghles; Maree, Mohammed (Frontiers in Surgery, 2023)
Introduction: Splenic artery aneurysm is considered an abnormal dilatation of the splenic artery layers greater than 1 cm in diameter. first described by Beaussier in 1770 and affects 1% of the population but carries a major risk for life-threatening complications of rupture in 3-10% of cases regardless of its congenital or acquired etiology. Presentation is highly variable from asymptomatic incidental discovery during routine imaging, to aneurysmal rupture causing acute abdomen, massive gastrointestinal bleeding, and hemorrhagic shock. Case Presentation: Herein, we present a 19-year-old male who presented with epigastric pain and abdominal rigidity associated with a moderate amount of peritoneal free-fluid that was found to be a ruptured SAA after urgent laparoscopy which was successfully managed with splenectomy, Conclusion: SAA encounters a rare etiology of acute abdomen and hemorrhagic shock but has a very high risk of mortality even upon immediate intervention, a very high level of suspicion is required, and a low threshold for surgical intervention in unstable patients presenting with abdominal pain.Although rare with only 1% prevalence (1), splenic artery aneurysm (SAA) is considered the third most common intra-abdominal aneurysm after the aortic and iliac arteries aneurysms (2) but being at high risk for the deadly complication of rupture is what makes it of crucial importance to diagnose and manage to prevent fatal outcomes even if it only happens in only 10% of cases (1). Patients may be asymptomatic, but the rupture is catastrophic with a mortality rate as high as 66% in aneurysms greater than 2cm. (3) SAA can be congenital or acquired, and atherosclerosis, hypertension, trauma, and septic embolism play a role in its development. Pregnancy and multiparity are known as risk factors in the development of SAA (4), and indeed, SAA is frequent in female patients as the femaleto-male ratio is 4:1 (3). Our 19-year-old-male patient who presented with sudden onset stabbing epigastric pain of one-hour duration, borderline blood pressure, and tachycardia associated with abdominal rigidity, was found to have free fluid on abdominal imaging, was lucky to survive acute abdomen and early signs of hemorrhagic shock after non-traumatic spontaneous rupture of his previously undiagnosed SAA.